Aspect Ratio-based Taguchi Method with An Application to the Friction Stir Welding of AA6062-T6 Alloy - Francis, Osita Prince; Ogunmola, Bayo Yemisi; Alozie, Nehemiah Sabinus; Oluwo, Adeyinka; Rajan, John; Jose, Swaminathan; Oke, Sunday Ayoola; Ibitoye, Ayomide Sunday (International Journal of Industrial Engineering and Engineering Management, 2025)
This research proposes a new method of modified Taguchi method based on aspect ratios of the parameters integrated with the present worth method for the determination of optimal parametric setting during the friction stir welding process. As a cornerstone feature in the optimization procedure, aspect ratios are uniquely formulated where single parameters are replaced with products of parameters, squares of a particular parameter multiplied by a parameter, and only squares of each parameter information that represent inputs for the determination of the orthogonal matrix, heading to the optimal parametric setting computations, ranks, and delta determination. A wide range of 83 formulations was considered. Unlike previous research, this article accounts for multiple combinations of aspect ratios greater than the members of parameters present in the factor-level framework in the traditional setting of the Taguchi scheme. A principal result reveals that when the parameters were interchanged from A, B, and C to ABC, A2C, A2 B, A2, B2, and C2, indicating tool till angle, tool rotational speed, and welding speed for A, B and C, respectively, the optimal parametric setting was 462000 (0.rpm.mm/min), 990 (0.mm/min), 12600 (0.rpm.90), 1960000rpm, 12100mm/min2. The result assists welding engineers in implementing optimal decisions during friction stir welding activities. The findings of this study stimulate welding engineers to establish sources of poor-quality welds and optimize the outputs while reducing welding costs.